GAMBARAN PENGETAHUAN PASIEN KANKER PAYUDARA TENTANG PENYAKIT DAN PENCEGAHAN METASTASE SEL KANKER PAYUDARA (Politeknik Kesehatan Kemenkes Bandung, 2020)
This research is motivated by the high mortality rate from breast cancer. Breast cancer is the highest cancer in women in the world. Based on estimates by the International Cancer Research Agency (IARC) in 2012, new cases (breast cancer) were 43.1 per 100,000 women, with a death toll of 12.9 per 100,000 women. The estimated incidence of breast cancer in Indonesia is 40.3 per 100,000 women or 48,998 new cases per year. Breast Cancer Research About Disease Prevention of Breast Cancer Cell Metastases by the Systematic Literature Review method by analyzing the results of research on breast cancer in 2010-2019. Results of the analysis Four results of the study showed a sufficient level of knowledge in the category. It is expected that nurses can seek health education about cancer so patients can better understand the disease that is happening by utilizing various health promotion media.